تمثلات تلاميذ الثالثة ثانوي "الجدد والمعيدين" لإدارة الزمن "دراسة ميدانية تشمل مؤسسات التعليم الثانوي بالمدينة الجديدة علي منجلي" قسنطينة - بن عبد المالك, عبد العزيز (Changement Social; No 06 (2019): revue change social, 2019)
يعد الزمن التعليمي من أهم العناصر الأساسية في تحديد نتائج العملية التربوية برمتها ودعامة من دعامات التحديث والتغيير. كما يعتبر شكلا من أشكال الرفع من المردودية البيداغوجية والجودة في الأداء التعليمي مما يسمح بضمان منتوج ذي نوعية عالية. ولما كان مفهوم الزمن يفيد في كثير من معانيه تنظيم وتدبير الحصص السنوية والأسبوعية واليومية لأنشطة المتعلم الفكرية والمهارية والعلائقية، بحيث يراعي هذا التنظيم الصحة الجسمية والنفسية للتلميذ محدثا توازنا وظيفيا يساعد في استقبال ومعالجة مختلف المعارف.  نحاول من خلال هذه الورقة البحثية اطلاعكم والكشف عن مكونات وبنية التمثّل؛ لإدارة و تدبير الزمن خاصة أثناء مرحلة المراجعة والمذاكرة لدى التلاميذ الذين يجتازون شهادة البكالوريا لأول مرة والمعيدين لها، معتمدين في ذلك على شبكة التداعيات. الكلمات المفتاحية : التمثلات -إدارةالزمن التدبير الزمني- امتحان البكالوريا Third year students -new and repeating- representation of time management -Field study involving the secondary schools in the new city Ali Mandjli- School time is an important element in determining the results of educational process and a pillar of modernization and change. It is considered as a form of increased pedagogic efficiency and quality in educational performance that guarantees a high quality product. Since the concept of time signifies the organization and management of annual, weekly and daily sessions of intellectual, skillful and relational activities of the learner, so that this organization takes into account the physical and psychological health of the student, creating a balanced function that helps receiving and processing different knowledge. We present the components and structure of the representation to manage school time, especially during the revision stage of students who pass the baccalaureate for the first time and repeating students, relying on the associations network. Keywords : Representations, time anagement, time handling, Baccalaureate exam.